Research on the composition and space utilization of residential neighborhoods in Old Lilong, Shanghai, China: mutual influence between streets and residences from the dual perspective of “activeness” and residential remodeling rate - Lin Chen; Kai Fang; Xinpeng Wang; Zhehan Zhang; Nobuaki Furuya (Journal of Asian Architecture and Building Engineering, 2022)
Alongside modern urbanization, traditional Lilong housing structures have undergone tremendous changes in internal and external spatial form and usage status in order to adapt to the needs of modern, social life. In these spontaneous transformations, the street “publicness” and the residential privacy create a set of contradictory relationships that affect the overall morphology of the neighborhood. Taking the traditional lane residential area of Xing’anli, Dongtai Road, Shanghai, China as an example, we analyze the relationship between street “activeness” and the rate of residential remodeling. We attempt to clarify the characteristics of street publicness and housing “privateness” in the traditional Lilong neighborhoods and their mutual effects. This contributes to a comprehensive, workable knowledge of traditional cities and has reference significance for future urban transformation. We analyze the space utilization characteristics of Lilong neighborhoods from two perspectives here. First, with the overflow articles as a medium, we explore the activeness characteristics of different types of roads using the SD method. Second, based on field surveying and mapping, we assess the remodeling characteristics of buildings around different types of roads through remodeling volume and rate statistics. We draw conclusions through careful analysis of the relationship between the street activeness and residential remodeling rate information.